PENGEMBANGAN MEDIA WAYANG TEMATIK PADA TEMA INDAHNYA NEGERIKU SEBAGAI PENDUKUNG SCIENTIFIC APPROACH KELAS IV SEKOLAH DASAR - Zafira, Herza; Artharina, Filia Prima (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
The encouraging background of this research is the learning process that still tends to make students bored. Lessons that do not attract the attention of students, lessons that have not used thematic media, and learning atmosphere that seemed less fun. This type of research is research and development by Borg & Gall. Subjects in this study were all students of grade IV SD Negeri 08 Tanjungrejo Kudus and SD Negeri 03 Klaling Kudus academic year 2016/2017. Subjects as many as 33 students. Data in this study were obtained through interviews, questionnaires (questionnaire analysis of student needs, questionnaire of teacher needs analysis, student response questionnaire, questionnaire validation of media and material experts and scientific approach questionnaire), observation and documentation. From the assessment by media expert validation and material 1, the percentage of 88.23% and 87.50% of the results obtained by the media expert and material 2 obtained 98.5% percentage and 98.43% of the results by media experts and material 3 obtained percentage 92,64% dan 93,75 and the final result of assessment from material expert 4 obtained by percentage 85,93% while questionnaire of student response get percentage 97,43% in SD N 08 Tanjungrejo and 98,75% in SD N 03 Klaling and also scientific questioner Approach is obtained percentage of 90,38% in SD N 08 Tanjungrejo and equal to 97,00% in SD N 03 Klaling. The conclusion is the thematic media is worthy of use and can be used as a supporter of the scientific approach on the theme of Beautiful Affairs Negeriku fourth grade elementary school students.